2019
DOI: 10.1111/sifp.12104
|View full text |Cite
|
Sign up to set email alerts
|

Using Evidence to Drive Impact: Developing the FP Goals Impact Matrix

Abstract: When designing a family planning (FP) strategy, decision‐makers can choose from a wide range of interventions designed to expand access to and develop demand for FP. However, not all interventions will have the same impact on increasing modern contraceptive prevalence (mCP). Understanding the existing evidence is critical to planning successful and cost‐effective programs. The Impact Matrix is the first comprehensive summary of the impact of a full range of FP interventions on increasing mCP using a single com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 88 publications
(93 reference statements)
1
9
0
Order By: Relevance
“…For example, evidence from Latin America showed that the CPR was 16.5 percentage points higher among insured women than uninsured women (Fagan et al 2017). Exposure to mass media programs can also increase modern contraceptive use in a variety of settings, and when coupled with interpersonal communication channels, had high impact with an odds ratio of 1.51 (Weinberger et al 2019). Global experience also shows that the most successful interventions are those that address both demand for and supply of FP services, as well as the underlying drivers of fertility, especially education.…”
Section: Best Global Practices and Evidence For Lowering Fertilitymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, evidence from Latin America showed that the CPR was 16.5 percentage points higher among insured women than uninsured women (Fagan et al 2017). Exposure to mass media programs can also increase modern contraceptive use in a variety of settings, and when coupled with interpersonal communication channels, had high impact with an odds ratio of 1.51 (Weinberger et al 2019). Global experience also shows that the most successful interventions are those that address both demand for and supply of FP services, as well as the underlying drivers of fertility, especially education.…”
Section: Best Global Practices and Evidence For Lowering Fertilitymentioning
confidence: 99%
“…Evidence from several studies has shown that if women are provided with comprehensive counseling and are proactively offered contraception from a range of choices as part of childbirth care, 20-50 percent of them will leave the facility with a method (HIPs 2017a). A review of impact shows that ) with an odds ratio of 1.15 (Weinberger et al 2019).…”
Section: Relationship Between Unmet Need and The Cpr Between 1985 And...mentioning
confidence: 99%
“…The matrix found that each approach had a positive impact on contraceptive use (mass media: median OR = 1.29; interpersonal communication: median OR = 1.51; and community group engagement: median OR = 1.29) (Weinberger et al. 2019 ).…”
Section: Sbc Approaches To Address Behavioral Drivers Are Evidence‐based and Cost‐effectivementioning
confidence: 99%
“…The Family Planning Goals Impact Matrix has calculated impact estimates on use of modern contraceptives based on a single comparable metric (odds ratios [OR])) for three specific SBC approaches documented in the HIPs. The matrix found that each approach had a positive impact on contraceptive use (mass media: median OR = 1.29; interpersonal communication: median OR = 1.51; and community group engagement: median OR = 1.29) (Weinberger et al 2019).…”
Section: Sbc Approaches To Address Behavioral Drivers Are Evidence-based and Cost-effectivementioning
confidence: 99%
“…Monitoring changes in modern contraceptive use provides valuable insight into the impact of a country's family planning (FP) program [1]. For over 2 decades the family planning community has relied on large national-scale surveys such as the Demographic and Health Survey (DHS) and the Multiple Indicator Cluster Survey (MICS) to track progress in family planning indicators, such as the modern contraceptive prevalence rate (mCPR) and unmet need for contraception [2,3].…”
Section: Introductionmentioning
confidence: 99%